9u-42=7(u-8)

Simple and best practice solution for 9u-42=7(u-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9u-42=7(u-8) equation:



9u-42=7(u-8)
We move all terms to the left:
9u-42-(7(u-8))=0
We calculate terms in parentheses: -(7(u-8)), so:
7(u-8)
We multiply parentheses
7u-56
Back to the equation:
-(7u-56)
We get rid of parentheses
9u-7u+56-42=0
We add all the numbers together, and all the variables
2u+14=0
We move all terms containing u to the left, all other terms to the right
2u=-14
u=-14/2
u=-7

See similar equations:

| 3+6r=27 | | 36–3(2–4x)=0 | | 6(w+2)-8w=30 | | c(4)=35 | | -8-9x=64+3x | | 16x+4x=40 | | 8-49x+1=16 | | -y/3=-10 | | 180x=5x+5 | | 51=3-12x | | 2j−16=2j= | | Y+7=3(x15) | | 8-(6x+-1)=99 | | (6u-5)^1/3=-5 | | m=217/31 | | -2=4w=6 | | 2j-16=2j= | | 8(b+1)+4=3(2b8)-16 | | 6(g-91)=30 | | 92-yy=74 | | Y+7=3x+15 | | 4x-(3×+13)=180 | | 1/3(6x-1)=30/5 | | 3(x-5=-2(5-4x) | | -897-x=-1619 | | 3x+2+5x-30=180 | | d/8-50=-43 | | 10w-3(2w-9)=23 | | -897-x=-1,619 | | 2j−16=2 | | 2.5x-4.5=11x-3 | | 8y^2-30y+27=8y |

Equations solver categories